2001
DOI: 10.1101/gad.895601
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of U4 and U6 interactions with the 5′ splice site using a S. cerevisiae in vitro trans-splicing system

Abstract: Spliceosome assembly has been characterized as the ordered association of the snRNP particles U1, U2, and U4/U6·U5 onto pre-mRNA. We have used an in vitro trans-splicing/cross-linking system in Saccharomyces cerevisiae nuclear extracts to examine the first step of this process, 5 splice site recognition. This trans-splicing reaction has ATP, Mg 2+, and splice-site sequence requirements similar to those of cis-splicing reactions. Using this system, we identified and characterized a novel U4-5 splice site intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1
2

Year Published

2001
2001
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 71 publications
(96 reference statements)
2
32
1
2
Order By: Relevance
“…The intriguing absence of the half-TPR domain in yeast Prp24 itself (Fig+ 1A) may indicate that its function is not required in budding yeast+ A more interesting possibility, supported by the presence of a half-TPR domain in the C. albicans Prp24 homolog, is that the function of the missing N-terminal domain is provided by a separate polypeptide+ The most likely candidate, based on sequence homology, is Prp39, a U1 snRNP component consisting solely of half-TPRs (Lockhart & Rymond, 1994)+ Although a functional association of Prp24 with the U1 snRNP has not been reported to date, the proposed switch of U6 for U1 at the premRNA 59 splice site (Staley & Guthrie, 1999) is one place where such an interaction might occur+ Indeed, it has recently been reported that nucleotides in both U4 and U6 can be crosslinked to the 59 splice site in a trans-splicing assay (Johnson & Abelson, 2001)+ Consistent with this hypothesis, we have observed a weak but reproducible two-hybrid interaction between Prp24 and Prp39 (our unpubl+ data)+ Further experiments in both the yeast and mammalian systems will be required to reveal the function of the enigmatic half-TPR domain+…”
Section: A Human Homolog and Its Implicationsmentioning
confidence: 99%
“…The intriguing absence of the half-TPR domain in yeast Prp24 itself (Fig+ 1A) may indicate that its function is not required in budding yeast+ A more interesting possibility, supported by the presence of a half-TPR domain in the C. albicans Prp24 homolog, is that the function of the missing N-terminal domain is provided by a separate polypeptide+ The most likely candidate, based on sequence homology, is Prp39, a U1 snRNP component consisting solely of half-TPRs (Lockhart & Rymond, 1994)+ Although a functional association of Prp24 with the U1 snRNP has not been reported to date, the proposed switch of U6 for U1 at the premRNA 59 splice site (Staley & Guthrie, 1999) is one place where such an interaction might occur+ Indeed, it has recently been reported that nucleotides in both U4 and U6 can be crosslinked to the 59 splice site in a trans-splicing assay (Johnson & Abelson, 2001)+ Consistent with this hypothesis, we have observed a weak but reproducible two-hybrid interaction between Prp24 and Prp39 (our unpubl+ data)+ Further experiments in both the yeast and mammalian systems will be required to reveal the function of the enigmatic half-TPR domain+…”
Section: A Human Homolog and Its Implicationsmentioning
confidence: 99%
“…U4/5Ј splice site interaction has been demonstrated in the yeast spliceosome using an in vitro trans-splicing system. The ϩ2 residue of the intron can cross-link to residues 75, 78, and 82 of U4 downstream of the U4/U6 helix I independent of the U2 association with the branch point, indicating that U4 RNA also contacts the pre-mRNA during its association with the spliceosome (10). By carrying out splicing at lower concentrations of ATP in a conventional cis-splicing reaction, we have been able to isolate the preactivated spliceosome and detected multiple cross-linked products of U4 to the pre-mRNA (data not shown).…”
Section: Dynamicmentioning
confidence: 99%
“…X1, appearing only in the active spliceosome, contains cross-links between the Lsm binding site of U6 and the intron sequence in a region ϳ30 bases downstream from the 5Ј splice site (21). X2a and X2b are cross-linked products between the 5Ј splice site and U6 in a region near the conserved ACAGA box (10). X2a, previously identified as dX2, accumulated in the spliceosome formed in NTC-depleted extracts (lane 2).…”
Section: Dynamicmentioning
confidence: 99%
See 2 more Smart Citations